2006
DOI: 10.1007/s00011-006-5196-x
|View full text |Cite
|
Sign up to set email alerts
|

The active metabolite of leflunomide, A77 1726, increases proliferation of human synovial fibroblasts in presence of IL-1β and TNF-α

Abstract: A77 1726 displays proliferative effects in presence of IL-1beta and TNF-alpha. Further elucidation of involved mechanisms may prove useful for the utilization of leflunomide, the development of related compounds or elaboration of new therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(50 reference statements)
0
3
0
1
Order By: Relevance
“…This approach was next applied to the production of the active metabolite of Leflunomide,20 which was approved for commercialisation under the name Teriflunomide (trade name Aubagio) by the FDA in 2012 for the treatment of multiple sclerosis 21. Indeed, the treatment of 5‐methyl‐4‐isoxazolecarboxylic acid with CDI followed by mixing with 4‐(trifluoromethyl)aniline hydrochloride during 5 h and then with water during 5 min produced Leflunomide as a fine suspension in water (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…This approach was next applied to the production of the active metabolite of Leflunomide,20 which was approved for commercialisation under the name Teriflunomide (trade name Aubagio) by the FDA in 2012 for the treatment of multiple sclerosis 21. Indeed, the treatment of 5‐methyl‐4‐isoxazolecarboxylic acid with CDI followed by mixing with 4‐(trifluoromethyl)aniline hydrochloride during 5 h and then with water during 5 min produced Leflunomide as a fine suspension in water (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…In another study; IL-36 receptor is expressed in human synovial fibroblast and human articular chondrocytes but there was no increase in IL36β levels in the inflamed human and mouse joints. Serum IL-36β levels were also similar in healthy controls with rheumatoid arthritis, osteoarthritis 29 . In another study which compared RA and psoriatic arthritis showed that IL-36α is expressed at similar levels in the synovium while psoriatic arthritis synovium expressed less IL-36Ra compared with RA.…”
Section: Discussionmentioning
confidence: 62%
“…Препарат является ингибитором митохондриального фермента дигидроортатдегидрогеназы (ДГО-ДГ), который необходим для синтеза пиримидина. Таким образом, под действием препарата снижается репликация аутореактивных лимфоцитов [34].…”
Section: терифлуномидunclassified